BEBERAPA SIFAT FISIS DAN KIMIA EKSTRAK TANIN - Gustan Pari (Pusat Penelitian dan Pengembangan Hasil Hutan, 1990)
The result of study on some physical and chemical properties of tannin ex tractiues prepared by using extraction method is presented in this report. Treatment conditions for tannin extractive were respectively fineness of 40 and 60 mesh, extraction temperature were: 60°C, 80°C, 100°C ahd raw material species for this experiment were Pinus merkusii, Rhizopora apiculata and Acacia decurrens.The result shows that the yield of tannin extroctives ranges from 0,5222,75%, tannin content: 2,9970,76%, moisture content: 0,002225,58%, solubility in cold water: 0,0963,50% and tannin content of residure ranges from 0,193,75%.